2022
DOI: 10.3390/biom12060794
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Electrospun Poly(amino acid) Nanofibers and Their Applications of Hemostasis and Wound Healing

Abstract: The timely and effective control and repair of wound bleeding is a key research issue all over the world. From traditional compression hemostasis to a variety of new hemostatic methods, people have a more comprehensive understanding of the hemostatic mechanism and the structure and function of different types of wound dressings. Electrospun nanofibers stand out with nano size, high specific surface area, higher porosity, and a variety of complex structures. They are high-quality materials that can effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 164 publications
0
31
0
Order By: Relevance
“…In the whole electrospinning process, the positive and negative poles of the high-voltage power supply were connected to the spinneret capillary and aluminum foil, respectively, which led to the formation of a high-voltage electrostatic field between the spinneret and aluminum foil [ 67 , 68 , 69 ]. As shown in Figure 1 , the purpose of grounding was to introduce the charge on the aluminum foil into the ground and ensure a safer experimental environment.…”
Section: Resultsmentioning
confidence: 99%
“…In the whole electrospinning process, the positive and negative poles of the high-voltage power supply were connected to the spinneret capillary and aluminum foil, respectively, which led to the formation of a high-voltage electrostatic field between the spinneret and aluminum foil [ 67 , 68 , 69 ]. As shown in Figure 1 , the purpose of grounding was to introduce the charge on the aluminum foil into the ground and ensure a safer experimental environment.…”
Section: Resultsmentioning
confidence: 99%
“…The significant variation in yields observed can be explained by the variation in micronutrient content present within the algal substrate. It has been widely reported that the concentrations of Ca 2+ , Zn 2+ , Co 2+ , Zn 2+ , Mg 2+ , Na 2+ , Fe 2+ and Mn 2+ impact the yields, molar mass and D/L ratios of the resulting material [ 32 , 39 , 40 , 43 , 44 , 46 , 47 , 48 , 49 ]. The variation in concentration of these minerals could be greatly affected by the location of cultivation or by the pre-treatment method (sterilisation) commercial L. digitata could have incurred before packaging and distribution [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning was initially an electrohydrodynamic method for converting the filament-forming polymers into nanofibers ( Wang Y et al, 2021b ; Chen, et al, 2022 ; Ji, et al, 2022 ). It has drawn increasing attention recently because active ingredients (including those for detecting glucose) can be easily encapsulated into the polymeric nanofibers to form a new kind of functional nanocomposites ( Wang M. et al, 2021 ; Zhang M. et al, 2022 ; Zhou Y. et al, 2022 ).…”
Section: Electrospun Glucose Sensorsmentioning
confidence: 99%